Effects of Friendly Parent-Children Communication on Children’s Interest in Education: A Study of Southern Punjab - Bhatti, Bilal; Dr. Sajjad Ali; Farrukh Nazir; Raza Majid (Journal of Peace, Development and Communication, 2021)
Parents-Children Communication remained an area of urgency to be addressed because the education of children revolves around the communication which was taken as granted by most of the parents. The research study was carried out across the Southern Punjab. The researcher selected the area due to low literacy rate and less socio-economic status. This research investigated the relationship between Parental-Children Communication, and children’s interest in education. The Emotional Security Theory (EST) and Social Learning Theory were applied to the study. All 6th grade children from Southern Punjab were considered as population of the study. The researcher used multistage sampling technique. The survey data was taken from a balanced sample of 1000 male and female children and analyzed through SPSS version-25. The study revealed that friendly Parent-Children Communication was positively associated with children’s interest in education. The study was found beneficial for the parents to redress their communication with children to build children’s interest in gaining education.